Minat Studi Lanjut ke Perguruan Tinggi Siswa Ditinjau dari Self-Efficacy dan Aspirasi Orangtua - Kemala Putri Kustiani; Dwi Yuwono Puji Sugiharto; Catharina Tri Anni (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2019)
This study aims to determine that the relationship between self-efficacy and parents aspiration with the interest in advanced studies to college of students either partially or jointly. This research uses correlation quantitative design. The sample used amounted to 160 of the population of 283 students with random sampling technique. Data collection tools use self-efficacy scales, parent`s aspiration scales, and the interest in advanced studies to college scales. We using simple linear regression and multiple linear regression to data analyzed. The result showed that there are significant correlations between (1) self-efficacy and the interest for collage, dan; (2) parents aspiration and the interest in advanced studies to college. Furthermore, relationship between self-efficacy and parents aspiration with the interests student in advance studies also had significant correlation. In this study it was also revealed that the contribution of the influence of self-efficacy and parents aspiration to the interests student in advance studies (to college) was 33.9%.